Peranan Sektor Kelautan dan Perikanan terhadap Pendapatan Asli Daerah (PAD) Kabupaten Fakfak - Randi Gandi Patiran (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
In the Outline of the State Direction in Chapter IV of the Sixth Phase of Five-Year Development, part F of the economic field point 2, it is said that "Marine and Fisheries Development is continued and more directed towards efforts to increase income and more directed at increasing the income and living standards of fishermen and advancing the level of quality of life in coastal villages through increasing the diversification of fish production to meet food and nutrition needs and increase export value. Marine and fisheries development in Fakfak Regency during the first long-term development has shown positive results that can be shown by a fairly high increase in production accompanied by an increase in community fish consumption, an increase in fishermen's income for the community, an increase in inter-island and export fish marketing, an expansion of employment and business opportunities in the marine and fisheries sector. This study aims to find out how the marine and fisheries sector affects the increase in Regional Original Revenue (PAD) of Fakfak Regency and to find out the impact of regional levies on the receipt of Daserah Original Revenue for the Marine and Fisheries Sector of Fakfak Regency. The research method used is a qualitative research method. Seeing the existing reality, the marine and fisheries sector has maximally made breakthrough efforts according to its role in order to increase Regional Original Revenue (PAD) as capital in regional development.